1998
DOI: 10.1161/01.cir.98.13.1268
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Efficacy, Clinical Safety, and Outcomes After Prolonged Platelet Glycoprotein IIb/IIIa Receptor Blockade With Oral Xemilofiban

Abstract: Xemilofiban inhibited platelet aggregation and was well tolerated during 28 days of long-term oral therapy. The observed trend in reduction of cardiovascular events in follow-up awaits confirmation in the larger-scale phase III study (EXCITE trial) currently in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 15 publications
5
34
0
1
Order By: Relevance
“…11 With oral administration, peaks and troughs (corresponding to the drug's half-life) exist in the level of platelet inhibition; these are not present with intravenously administered IIb/IIIa inhibitors. In addition, substantial variability between patients in the level of inhibition has been observed with all oral agents 12,13 ; this is related in part to differences in bioavailability. As such, with a fixed dose, some orbofibantreated patients have as high as 100% inhibition at peak and others as low as 0% to 20% inhibition at trough.…”
Section: Potential Explanations For Lack Of Benefitmentioning
confidence: 99%
“…11 With oral administration, peaks and troughs (corresponding to the drug's half-life) exist in the level of platelet inhibition; these are not present with intravenously administered IIb/IIIa inhibitors. In addition, substantial variability between patients in the level of inhibition has been observed with all oral agents 12,13 ; this is related in part to differences in bioavailability. As such, with a fixed dose, some orbofibantreated patients have as high as 100% inhibition at peak and others as low as 0% to 20% inhibition at trough.…”
Section: Potential Explanations For Lack Of Benefitmentioning
confidence: 99%
“…The Oral Glycoprotein IIb/IIIa Receptor Blockade to Inhibit Thrombosis (ORBIT) trial was a randomized dose-ranging trial of xemilofiban in patients undergoing percutaneous intervention. 34 Peak inhibition of platelet aggregation was similar following the same dose of xemilofiban administered on Days 14 and 28 of the trial. The time to peak blood level following the same dose of xemilofiban was reduced from 4 h following the first dose of drug to 2 h with steady-state dosing during chronic therapy.…”
Section: Xemilofibanmentioning
confidence: 84%
“…The time to peak blood level following the same dose of xemilofiban was reduced from 4 h following the first dose of drug to 2 h with steady-state dosing during chronic therapy. 34 Most bleeding events were observed during the first 2 weeks of therapy on a three-times daily dosing regimen. 34 …”
Section: Xemilofibanmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, large phase III trials of these oral agents have shown no therapeutic benefit and development of most of these agents has been abandoned. A major problem with GPIIb/IIIa antagonists is a relatively narrow safety/efficacy window, since high doses cause an unacceptable compromise to haemostasis, accompanied by wide pharmacokinetic and pharmacodynamic variations between individuals [Kereiakes et al, 1996[Kereiakes et al, , 1998Kleiman et al, 1995;Lehne et al, 1998;Simoons et al, 1994;Simpfendorfer et al, 1997;Storey et al, 1999;Tcheng et al, 1995]. On this background, it may be hypothesised that P 2T receptor antagonism offers an alternative strategy to GPIIb/IIIa antagonists.…”
Section: P 2t Receptor Antagonists Vs Gpiib/iiia Antagonistsmentioning
confidence: 99%